Reproductive control by others: means, perpetrators and effects. (8th January 2019) - Rowlands, Sam; Walker, Susan
Abstract : Background: Reproductive control of women by others comprises a wide range of behaviours, from persuasion to pressure such as emotional blackmail, societal or family expectations, through to threats of or actual physical violence. It is defined as behaviours that interfere with women's reproductive autonomy as well as any actions that pressurise or coerce a woman into initiating or terminating a pregnancy Method: Narrative review based on a search of medical and social science literature. Results: Reproductive control by others includes control or coercion over decisions about becoming pregnant and also about continuing or terminating a pregnancy. It can be carried out by intimate partners, the wider family, or as part of criminal behaviour. One form is contraceptive sabotage, which invalidates the consent given to sex. Contraceptive sabotage includes the newly-described behaviour of 'stealthing': the covert removal of a condom during sex. Reproductive control by others is separate from intimate partner violence but there are similarities and the phenomena overlap. Reproductive control by others is reported by as many as one quarter of women attending sexual and reproductive healthcare services. Those treating such women should be familiar with the concept and how to ameliorate its effects. Screening questions for its detection have been developed as well as interventions to reduce its risk. Conclusions: Reproductive control by others is common and those working in women's health should be familiar with the concept and with screening tools used to detect it.